2019
DOI: 10.1017/s1368980019002805
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary patterns and chronic kidney disease in a middle-aged Chinese population

Abstract: Objective:To explore the relationship between dietary patterns and risk of chronic kidney disease (CKD) in Chinese adults aged 45–59 years.Design:Dietary data were collected using a semi-quantitative FFQ. Factor analysis was used to identify the major dietary patterns. Logistic regression models were applied to clarify the association between dietary patterns and the risk of CKD.Setting:The present study population was a part of the population-based Nutrition and Health Study performed in the city of Hangzhou,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 45 publications
(72 reference statements)
2
24
0
Order By: Relevance
“…This cross-sectional study revealed that the western dietary pattern, characterized by higher intake of soft drinks, fast food, mayonnaise, cakes, cookies, red meat, sweets, refined grains, salty snacks, French fries, high-fat dairy products, and organ meats, was associated with the increased risk of CKD after adjustment for multiple co-variants in adults with high blood pressure in Iran. In agreement with our findings, several studies have also reported a significant association between adherence to the Western dietary pattern and the risk of kidney function decline (5,(7)(8)(9)(10). In the TLGS, the high fat, high sugar dietary pattern was associated with a 49% increased odds of the incidence of CKD after 6.1 years of follow-up (8).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This cross-sectional study revealed that the western dietary pattern, characterized by higher intake of soft drinks, fast food, mayonnaise, cakes, cookies, red meat, sweets, refined grains, salty snacks, French fries, high-fat dairy products, and organ meats, was associated with the increased risk of CKD after adjustment for multiple co-variants in adults with high blood pressure in Iran. In agreement with our findings, several studies have also reported a significant association between adherence to the Western dietary pattern and the risk of kidney function decline (5,(7)(8)(9)(10). In the TLGS, the high fat, high sugar dietary pattern was associated with a 49% increased odds of the incidence of CKD after 6.1 years of follow-up (8).…”
Section: Discussionsupporting
confidence: 91%
“…of the previous studies have been done in East Asia (9,11), Europe (10), and the USA (7,12). Furthermore, to the best of our knowledge, most research to investigate the association between the dietary pattern and renal dysfunction has been conducted in healthy populations (7)(8)(9)(10)12) or diabetics (11) and there is a lack of data on patients with high blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, a substantial amount of research has explored the in uence of diet, a modi able risk factor on diabetes risk, and the majority of these studies have examined individual foods or nutrients and their effect on diabetes [7][8]. Nevertheless, in reality, individuals do not eat nutrients or foods in isolation, but consume meals containing combinations of many foods and nutrients that possibly interact with each other [9]. Consequently, dietary pattern analysis is now widely accepted in the realm of nutritional epidemiology as a more recognizable approach for assessing the relationship between diet and diseases, because it takes into account the complexity of whole-diet and potentially facilitates nutritional recommendations [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, a substantial amount of research has explored the influence of diet, a modifiable risk factor on diabetes risk, and the majority of these studies have examined individual foods or nutrients and their effect on diabetes [ 7 , 8 ]. Nevertheless, in reality, individuals do not eat nutrients or foods in isolation, but consume meals containing combinations of many foods and nutrients that possibly interact with each other [ 9 ]. Consequently, dietary pattern analysis is now widely accepted in the realm of nutritional epidemiology as a more recognizable approach for assessing the relationship between diet and diseases, because it takes into account the complexity of whole-diet and potentially facilitates nutritional recommendations [ 10 ].…”
Section: Introductionmentioning
confidence: 99%